Augmented Reality dalam Pembelajaran - Hendra Nelva Saputra (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2020)
Augmented reality is one of the developing technologies and has a good potential to apply in the teaching and learning process. Augmented reality facilitates and improves the quality of teaching and learning process because of the combination of virtual objects with real environments by taking advantage of the use of technology. Augmented reality visualizes abstract concepts for understanding and the structure of an object model. A main characteristic for a medium classified as an augmented reality is combining real and virtual objects, integrated in real and virtual objects, and a real-time interaction. The use of augmented reality in teaching and learning has already been applied to many subjects, such as the concepts of space and geometry in mathematics, the human digestive system of biology, the introduction of traditional houses in social science, and the introduction of wudhu procedure in early childhood education or kindergarten (PAUD/TK) kids.